Preparation and Optical Properties of SPION/SrMoO4:Er3+, Yb3+ Composites via Cyclic Microwave-Assisted Metathetic Route - Sung Lim, Chang (Asian Journal of Chemistry, 2013)
Er3+/Yb3+ co-doped SrMoO4 (SrMoO4:Er3+/Yb3+) composites with superparamagnetic iron oxide nanoparticles (SPIONs) incorporated were successfully synthesized by a cyclic microwave-assisted metathetic method, followed by heat-treatment. The microstructure exhibited well-defined and homogeneous morphology with SrMoO4:Er3+/Yb3+ particle sizes of 1-2 μm and Fe3O4 particle sizes of 0.1-0.5 μm. The Fe3O4 particles were self-preferentially crystallized and immobilized on the surface of SrMoO4:Er3+/Yb3+ particles. The synthesized SPIONs/SrMoO4:Er3+, Yb3+ composites were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Optical properties were examined using photoluminescence emission data and Raman spectroscopy.